The who's who of a hydrogen market ramp-up: A stakeholder analysis for Germany - David Schlund; Simon Schulte; Tobias Sprenger (Institute of Energy Economics at the University of Cologne (EWI), 2021)
The interest in low-carbon hydrogen technologies is growing fast in politics and the economy. The ramp-up of a hydrogen market is a critical phase, which requires the engagement and coordination of many heterogeneous stakeholders. A better understanding of who these stakeholders are and what relationships, chances, and risks they perceive is crucial to guide a hydrogen market ramp-up. This paper conducts a stakeholder analysis for Germany with a focus on the market ramp-up period. Interviews with 36 hydrogen experts, literature, and stakeholders from 78 real-world hydrogen research and demonstration projects are analysed with qualitative content analysis and social network analysis. In total, 49 stakeholder groups are identified and defined accordingly. Our results indicate that established stakeholders' roles will significantly change in a future hydrogen market. Risks range from economic and supply chain risks to impacts on international policy. Chances are found along economic, ecological, and political dimensions. Political intervention during the market ramp-up should mostly focus on the economic gap between low-carbon hydrogen and fossil alternatives and on prioritising the allocation of scarce hydrogen supply on heterogeneous demand. Simultaneously, a long-term strategy should be envisaged to guarantee a competitive and nondiscriminatory hydrogen market in the future.
Keywords: L52; L94; L95; M21; Q40; Q42; 330; Hydrogen market; Hydrogen economy; Stakeholder analysis